Comparison of the effects of esomeprazole 40 mg, rabeprazole 20 mg, lansoprazole 30 mg, and pantoprazole 40 mg on intragastric pH in extensive metabolizer patients with gastroesophageal reflux disease - ÇELEBİ, ALTAY; Aydin, Dincer; Kocaman, Orhan; Konduk, Bugra Tolga; Senturk, Omer; Hulagu, Sadetin (My University, 2016)
Background/Aims: Studies on the therapeutic efficacy of proton pump inhibitors (PPIs) in patients with gastroesophageal reflux disease (GERD) have been recently published. In most of these studies, comparison of only two PPIs have been made. There are few studies on the comparison of four or more PPIs. We aimed to compare the acid inhibitory effects of esomeprazole 40 mg, rabeprazole 20 mg, lansoprazole 30 mg, and pantoprazole 40 mg on days 1 and 5 of treatment in patients with GERD, who were extensive metabolizers in regard to the CYP2C19 genotype.